The Influence of Squat Body Training and Vertical Jump Training on the Results of Smash Block Volleyball Game Extracurricular Students - Octariani, Dewani; Lian, Bukman; Akhbar, M Taheri (Journal of Social Work and Science Education, 2023)
The problem in this research is still the low ability of players to perform block techniques. It can be seen that during training many cannot block the ball when they want to block. Students who have not mastered the correct blocking techniques and students who lack confidence when they want to block. Lack of balance when jumping when blocking. The purpose of this study was to determine the results of Squat Body Training and Vertical Jump exercises on the results of the Smash Block Volleyball Game of Extracurricular Students SMP Negeri 38 Palembang. This research method uses experimental research. This research design uses a pretest-posttest design. The study provided the treatment of exercise A and exercise B without not comparing with the results of the control group. The independent variable in this study was in the form of body training squat exercises and vertical jump exercises, while the dependent variable was in the form of smash block results of extracurricular students of SMP Negeri 38 Palembang. In pretest and posttest charts. The data analysis technique used in this research using SPSS 26 is by using anova at a significant level of α= 0.05. The results showed that there is influence of squat body training and vertical jump training on the results of smash block volleyball game extracurricular students.